It Takes a Community--The Open Source Challenge. - Xin, Reynold; McKinney, Wes; Gates, Alan; McCubbin, Chris (Communications of the ACM, 2022)
A discussion about open source computer software development and the notion of an open source community is presented that includes Databricks chief architect Reynold Xin, Hortonworks co-founder Alan Gates, and Ursa Labs founder Wes McKinney.